Meaningful community participation for effective development of sustainable tourism: bibliometric analysis towards a quintuple helix model - Iqbal, Aatif; Ramachandran, Sridar; Siow, May Ling; Subramaniam, Thanam; Mohammad Afandi, Syamsul Herman (Elsevier, 2022)
Meaningful community participation in tourism is considered a prerequisite for sustainable development at any tourist destination. Due to the growing desirability for development on more sustainable grounds in developed and developing countries, a considerable surge in the emphasis on significance of community participation in tourism sector has been observed in recent years. This led to an increase in the publication of literature on this important and widely recognized phenomenon, both for better understanding and practical reasons. However, there is still no clear picture of the degree and direction in which community participation research in tourism has grown. To address this issue, the current study tried to comprehensively look into the existing state of research in this area of study. This article provides a detailed insight into the literary landscape of community participation research in tourism. A bibliometric analysis of 649 articles screened out of 1434 publications retrieved from Scopus database was conducted. The systematic descriptive and network analysis of bibliometric data using the Biblioshiny and VOSviewer tools yielded some intriguing results. The findings confirm the centrality of community participation in achieving the goal of sustainable development of tourism. This paper while filling the unaddressed gap of the absence of a comprehensive bibliometric study on community participation research in tourism, improves our understanding of the literary landscape and thematic evolution of academic discourse during nearly four decades. Furthermore, a quintuple helix model is proposed to explore and understand the dynamic literary landscape and how it grows and evolves, thus facilitating future research in this area. Management implications: 1. Meaningful community participation is the key to the sustainable development of tourism at any destination. 2. Despite the complexities involved, the potential role of community participation in mitigating the negative impacts of tourism and its contribution towards achieving sustainable development goals cannot be overlooked. 3. Meaningful community participation should be complemented by socio-economic and political empowerment at tourist destinations. 4. The rapid growth in literature on community participation as explained by the quintuple helix model points towards the growing realization among academicians and practitioners regarding the need for meaningful engagement of destination communities in tourism development.